Comparison of Conventional and Wiper Inserts on Surface Roughness During Hard Turning of AISI 410 - Rangaraju, Adithya (Journal of Advanced Mechanical Engineering Applications, 2020)
This work focuses on the study of the effect of wiper inserts on surface roughness over conventional inserts during turning of AISI 410 steel by means of the all-gear lathe in dry condition with a constant depth of cut. To evaluate the influence of wiper inserts and to predict the surface roughness, modeling of this process is done. Design of experiments is based on the full factorial design for a three-factorial two-level design. Cutting speed, feed, and type of inserts are taken as input parameters and surface roughness and dynamic force are taken as a response. To evaluate the significance of input parameters and their interactions, ANOVA was used. Type of insert was found to be the most influencing parameter followed by feed influencing surface roughness. Feed was found to be the most influencing parameter affecting dynamic force. The optimum parameters for minimum surface roughness are: wiper type insert, cutting speed of 150 (m/min) and feed of 0.15 (mm/rev).